"It Just Feels Useless": Views of Economically Marginalized Women of Color on Prenatal Telehealth [A236]. (May 2022) - Dickens, Molly; Franck, Linda; Scott, Karen; Dy, Eric
Abstract : INTRODUCTION: Virtual prenatal care has spiked during the COVID-19 pandemic, yet most research has neglected to consider care satisfaction from individuals at highest risk for poor health care experiences and outcomes. METHODS: We recruited economically marginalized, pregnant individuals of color to share their experiences with telehealth prenatal care for a survey- and text-message-based study. A pre-study survey assessed level of trust in providers (1–5 score) and overall care satisfaction (CSAT score; 1–10). After individual appointments, participants assigned appointment-based CSAT scores alongside narrative feedback. Quantitative data were analyzed using descriptive statistics. Qualitative data were analyzed using directed thematic analysis. RESULTS: A total of 13 participants engaged in the study from May to July 2020. Most participants identified as Black/African American, with reported household income below 50, 000/year. Most participants rated trust in providers positively. For care satisfaction, telehealth delivery was generally viewed negatively within the scope of overall care. For individual appointments, CSAT scores for in-office visits were higher (median, 9; IQR, 1; n=35) than for telehealth visits (median, 6; IQR, 4; n=11). Participants' narratives reflected three themes: relationship/trust with provider, information sharing/support, and maternal/fetal assessment. In-person appointment narratives contained more positive language, while telehealth narratives contained more negative language. CONCLUSION: Most participants report feeling negative and less satisfied with telehealth with dissatisfaction centered on level of information provided and inability to physically evaluate their health and their baby's health. As remote prenatal care expands, there is an urgent need to engage patients as partners in the design and evaluation of its use and to augment telehealth with technology to objectively measure maternal and fetal health.